2017
DOI: 10.1039/c7ra07063b
|View full text |Cite
|
Sign up to set email alerts
|

Toward improved mechanical strength, oxidative stability and proton conductivity of an aligned quadratic hybrid (SPEEK/FPAPB/Fe3O4-FGO) membrane for application in high temperature and low humidity fuel cells

Abstract: The peak proton conductivity of aligned SPFSGF-5 membrane at 120 C under 20% RH is 11.13 mS cm À1, which is 1.44 fold better than that of pristine SP membrane (7.68 mS cm À1 ). In contrast, under identical operating conditions, the Nafion-112 membrane exhibited a peak proton conductivity of 9.78 mS cm À1 , a 1.13 fold lower conductivity compared to aligned quadratic hybrid membrane. Furthermore, the aligned quadratic hybrid membrane exhibited lower H 2 and O 2 gas permeability compared to pristine SP and unali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 59 publications
6
76
0
Order By: Relevance
“…The calculated electrical conductivity for the Naon/SGF-3 membrane (0.37 mS cm À1 ) is 3.08 fold higher than that of Naon/GO-3 (0.12 mS cm À1 ) and 17.61 fold higher than that of pristine Naon membrane (0.021 mS cm À1 ), due to high electrical conductivity and percolation threshold of Fe 3 O 4 -SGO. 2 However, the obtained electrical conductivity of the Naon/Fe 3 O 4 -SGO membrane is generally less i.e., lesser than the level which can affect the open circuit voltage of membrane during PEMFC operation.…”
Section: 55mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated electrical conductivity for the Naon/SGF-3 membrane (0.37 mS cm À1 ) is 3.08 fold higher than that of Naon/GO-3 (0.12 mS cm À1 ) and 17.61 fold higher than that of pristine Naon membrane (0.021 mS cm À1 ), due to high electrical conductivity and percolation threshold of Fe 3 O 4 -SGO. 2 However, the obtained electrical conductivity of the Naon/Fe 3 O 4 -SGO membrane is generally less i.e., lesser than the level which can affect the open circuit voltage of membrane during PEMFC operation.…”
Section: 55mentioning
confidence: 99%
“…Graphene is a single atom thick two-dimensional layer of sp 2 -hybridized carbon discovered by Geim et al, 20 and is associated with exceptional extended surface, unique p-bond delocalized hexagonal structure, excellent thermomechanical stability and high young's modulus that are benecial to its wide use in the elds of sensors, 21 catalysis, 22 adsorption, 23 nanoelectronics 24 and energy conversion and storage. [25][26][27] For the integration of graphene into PEM, it is essential to functionalize/oxidize sp 2 -hybridized carbon networks to convert the material as a protonic conductor and electronic insulator.…”
Section: -4mentioning
confidence: 99%
“…The composite membranes exhibited excellent H + conductivity, mechanical strength, and single cell performance at low humidity. 12 Cui et al prepared CNTs coated with silica as an additive to SPEEK-based membranes. The hydrophilic, insulated silica on CNTs prevented short circuit in the membrane and facilitated efficient dispersion of the filler into the polymer matrix through the interfacial interactions which resulted to good physiochemical properties.…”
Section: Funding Informationmentioning
confidence: 99%
“…Vinothkannan et al fabricated an aligned quadratic composite membrane based on SPEEK/fluorinated poly(arylene propane biphenyl) (FPAPB) using Fe 3 O 4 anchored on functionalized graphene oxide as the inorganic additive. The composite membranes exhibited excellent H + conductivity, mechanical strength, and single cell performance at low humidity . Cui et al prepared CNTs coated with silica as an additive to SPEEK‐based membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide nanomaterials are more promising fillers that have recently attracted an increasing research interest toward fuel cell applications because of their hygroscopic nature besides the proton conductivity of acidic sites . In addition, diminishing of fuel crossover and enhancing of the mechanical and thermal strength has been adequately satisfied by modification of these nanomaterials . For instance, Sigwadi et al impregnated a ZrO 2 ‐CNT nanoparticle into a Nafion polymer matrix and found that the mechanical properties and water retention of the nanocomposite membrane was enhanced compared with the plain Nafion 117.…”
Section: Introductionmentioning
confidence: 99%